2003
DOI: 10.1126/science.1086957
|View full text |Cite
|
Sign up to set email alerts
|

Untangling Desmosomal Knots with Electron Tomography

Abstract: Cell adhesion by adherens junctions and desmosomes relies on interactions between cadherin molecules. However, the molecular interfaces that define molecular specificity and that mediate adhesion remain controversial. We used electron tomography of plastic sections from neonatal mouse skin to visualize the organization of desmosomes in situ. The resulting three-dimensional maps reveal individual cadherin molecules forming discrete groups and interacting through their tips. Fitting of an x-ray crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
217
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(235 citation statements)
references
References 44 publications
14
217
2
2
Order By: Relevance
“…The structures of N-, E-, and C-cad- herin observed by crystallography and electron microscopy have shown end-and-end interactions that involve either EC1 or EC1-2 (4, 10 -18). Moreover, the recent interpretation of desmosomal cadherin interactions as revealed by electron microscopic tomography clearly reveals flexible tip-to-tip associations between the N termini of the molecules (17). Our findings are consonant with these studies, but in addition we have now demonstrated that the first two domains of N-cadherin are the minimal essential elements for the molecule to generate homophilic adhesion.…”
Section: Discussionsupporting
confidence: 79%
“…The structures of N-, E-, and C-cad- herin observed by crystallography and electron microscopy have shown end-and-end interactions that involve either EC1 or EC1-2 (4, 10 -18). Moreover, the recent interpretation of desmosomal cadherin interactions as revealed by electron microscopic tomography clearly reveals flexible tip-to-tip associations between the N termini of the molecules (17). Our findings are consonant with these studies, but in addition we have now demonstrated that the first two domains of N-cadherin are the minimal essential elements for the molecule to generate homophilic adhesion.…”
Section: Discussionsupporting
confidence: 79%
“…Chemically-fixed or HPF/FSF intestinal samples were infiltrated, embedded, polymerized, sectioned and stained as previously described (He et al, 2003). Selected regions of 70 -200 nm sections were examined using an FEI T12 G2 Electron Microscope operating at 120 kV, and projection images were recorded on a Gatan 894 2K × 2K CCD camera (Gatan Corporation).…”
Section: Embedding and Electron Microscopymentioning
confidence: 99%
“…Electron microscopy (12,13,24,31), X-ray crystallography (10,11,15,22), NMR (26,32), mutational experiments (22), and domain swapping experiments (33) have implicated the EC1 domain in cadherin trans interactions. However, direct force measurements (16)(17)(18) supported by cell attachment and bead binding assays (19) showed 3 distinct adhesive alignments interpreted as the overlap of opposing EC1-5, EC1-3, and EC1 domains.…”
mentioning
confidence: 99%
“…A widely accepted model as summarized in textbooks (6) and recent review articles (1,(7)(8)(9) is that the functional unit of cadherin adhesion is a cis dimer formed by binding of the extracellular domains of 2 cadherins on the same cell surface. Cell-cell adhesion is initiated by the formation of trans adhesive complexes between the EC1 domains of cadherin cis dimers on opposing cell surfaces (1,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Strong cadherin adhesion may also require trans binding along additional EC domains (16)(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation